EFFECTS OF MOTORIC ABILITIES ON THE SPECIFIC MOTORIC ABILITIES OF FOOTBALL PLAYERS AGED BETWEEN 14 AND 16 ( - Arben Osmani; Dritan Mamaj (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2014)
Introduction: The research issue of this work is to examine the effect of motoric abilities on the specific motoric abilities with football players aged from14 to 16. According to the research issue, the following task was set: to establish the influence of the predictor system of six motoric tests on the two-criterion specific motoric tests. Methods: The group of tested persons in this research consists of 54 male football players aged from 14 to 16, who had active training in football club Prishtina. Their active football experience was two years at least. The sample of variables covers 6 motoric and 2 specific motoric variables. For each space individually there are calculated basic statistic indexes and the effect of the motoric abilities on the specific motoric abilities is established through the linear regressive analysis. Results: From the obtained results, presented in the 3 tables, the conclusion follows that the motoric variables had significant participation in the prediction of success in acquiring specific motoric abilities that are an important part of football. Discussion: Results similar to those obtained in this research are also evident with: Malina (2003), Swenson, & Drust (2005), Vaeyens, et al. (2006), Reilly, et al. (2000) and other eminent authors. We can confidently state that activities in which the trained football players were engaged show promise of high sports achievements. References: Malina RM (2003). Growth and maturity status of young soccer players. In T Reilly & AM Williams (eds.) Science and Soccer. Routledge, New York. Reilly T, Williams AM, Nevill A, Franks A (2000). Journal of Sport Sciences, 18, 695-702. Svensson M, Drust B (2005). Testing soccer players. Journal of Sports Sciences, 23(6), 601-18. Vaeyens R, Malina R M, Janssens M (2006). Br J Sports Med, 40, 928-34.